True Griceanism: Filling the Gaps in Callender and Cohen's Account of Scientific Representation. Issue 3 (July 2021) - Ruyant, Quentin
Abstract : Callender and Cohen have proposed to apply a "Gricean strategy" to the constitution problem of scientific representation. They suggest that scientific representation can be reduced to stipulation by epistemic agents. This account has been criticized for not making a distinction between symbolic and epistemic representation and not taking into account the communal aspects of representation. These criticisms would not apply if Grice's actual strategy were properly employed. I transpose Grice's strategy to epistemic representation. The main novelty of the resulting account is a distinction between contextual representational use and general representational status, which I address using the notion of indexicality.